Further Exploring the Brain–Skin Connection: Stress Worsens Dermatitis via Substance P-dependent Neurogenic Inflammation in Mice - Pavlovic, Sanja; Daniltchenko, Maria; Tobin, Desmond J.; Hagen, Evelin; Hunt, Stephen P.; Klapp, Burghard F.; Arck, Petra C.; Peters, Eva M.J. (Journal of investigative dermatology, 2008)
A neurogenic component in atopy and allergy is evident and potentially of great pathogenic relevance. Stress was recently shown to activate elements of this component and is vividly discussed as a cause of exacerbation. However, to date, scientific proof of stress-induced neuronal plasticity and neuro-immune interaction in atopy or allergy remains lacking. Here we show early evidence that exposure to sound stress and atopic dermatitis-like allergic dermatitis (AD) equipotently raise the number of cutaneous nerve fibers containing the prototypic stress neuropeptide substance P (SP) in mice. Stress increases AD readout parameters by at least 30% (eosinophil infiltration, vascular cell adhesion molecule-positive blood vessels, epidermal thickness). This dramatic pathologic exacerbation is associated with increased neurogenic inflammation (degranulated mast cells; interstitial neuropeptidergic dense core granules, mast cell apoptosis, endothelial gaping). Key features of AD exacerbation could not be induced in mice lacking the neurokinin-1 SP receptor (NK1). Interestingly, stress had no significant additional effect on CD4+ cell number, but shifted the cytokine profile toward TH2 in skin. Thus, we conclude that stress primarily exacerbates AD via SP-dependent cutaneous neurogenic inflammation and subsequent local cytokine shifting and should be considered as a therapeutic target, while it offers a convincing pathogenic explanation to affected patients and their frustrated physicians alike.